Very first patient gift in a general practitioner’s career and the impact of this event on physician-patient relationship - Vesna Kos (Medicinski glasnik, 2018)
Aim: To describe experiences, feelings and reactions of general practitioners (GPs) to the very first patient gift in the career, considering the impact on physician-patient relation (PPR). Methods: A representative sample of the Croatian GPs (N=265) filled in a supervised paper-based, researcher-led questionnaire. The response rate was 95.7%. Three independent analysts coded and analysed respondents' descriptions. The results were analysed using the descriptive statistics, χ²-test, and φ-coefficient of correlation. Results: The GPs received the very first patient's gift (FG) already as students (2.6%), during internship (41.5%), and at the latest after being a doctor for one year. After 2-42 years of practice, 95.1% of GPs described their FGs. Typical gifts were coffee and/or sweets (66%). Dominant feeling of GPs on receiving the FG was discomfort (33%); only 22% felt good; just 26% reacted with composure. The outcome regarding the physician-patient relationship (PPR) ranged from the debacle (9%), through mutual discomfort (13%) or a routine reaction (38%), to smiles and mutual pleasure (40%). In 18% they tried to behave properly, considering the patient's best interest, despite their own discomfort. In 29% of cases, the patient took the role of teacher, supporting the young physician. The PPR was not improved in 3/5 of cases where the FG was described. Conclusion: Receiving the FG is an impressive and deeply touching event, remembered many years afterwards. Without prior instructions, Croatian GPs mostly reacted in a confused manner. The missed opportunity of improving PPR in 60%, and patients' help instead of teachers' suggest the need for education.
Keywords: Family Medicine; Gift Giving; Ethics; Education